Institutions and economic growth in Asia the case of Mainland China, Hong Kong, Singapore and Malaysia - Huang, Flora Xiao; Yeung, Wai Ho (Routledge economic growth and development series, 2018)
This book explores the role of institutions in economic growth, looking in particular at specific Asian countries and at particular cities within those countries. It considers a wide range of factors besides institutions, including the law, cultural factors and overall government arrangements. The book's conclusions as to which factors have the greatest impact will be of considerable interest to economists of Asia and those interested in economic growth more widely.